Analysis of Students’ Creativity Level through Upcycling Crafts from Used Plastic in Class IV Elementary School - Ari Nurendah Lasma Wati; Deasylina da Ary (Universitas Negeri Malang, 2025)
Abstract: This study aims to analyze the level of creativity of fourth-grade students of SDN Tidar 4 Magelang City through upcycling crafts from used plastic in fine arts learning. The research method used in this research activity is descriptive qualitative, focusing on three problem formulations: 1) the environment of SD Negeri Tidar 4, 2) the process of learning fine arts crafts from used plastic, and 3) the level of student creativity in producing upcycle crafts. Data were collected through observation, interviews, and documentation. Data validity was tested using triangulation of sources and techniques. The subjects in this study were all students and teachers of grade IV SDN Tidar 4, totaling 24 students. The results of this study revealed that the majority of students at SDN Tidar 4 showed sufficient creativity in learning fine arts through making upcycled crafts from used plastic. However, there is still a small number of students who need more motivation in order to express their creativity in creating works from used plastic cups. This is due to their fear of trying something new and lack of experience in interacting with art. Abstrak: Penelitian ini bertujuan untuk menganalisis tingkat kreativitas siswa kelas IV SDN Tidar 4 Kota Magelang melalui kerajinan daur ulang dari plastik bekas dalam pembelajaran seni rupa. Metode penelitian yang digunakan dalam kegiatan penelitian ini adalah deskriptif kualitatif, dengan fokus pada tiga rumusan masalah: 1) lingkungan SD Negeri Tidar 4, 2) proses pembelajaran kerajinan seni rupa dari plastik bekas, dan 3) tingkat kreativitas siswa dalam menghasilkan kerajinan daur ulang. Pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Keabsahan data diuji dengan triangulasi sumber dan teknik. Subjek dalam penelitian ini adalah seluruh siswa dan guru kelas IV SDN Tidar 4 yang berjumlah 24 siswa. Hasil penelitian ini mengungkapkan bahwa sebagian besar siswa di SDN Tidar 4 menunjukkan kreativitas yang cukup dalam pembelajaran seni rupa melalui pembuatan kerajinan daur ulang dari plastik bekas. Namun, masih ada sebagian kecil siswa yang memerlukan lebih banyak motivasi untuk dapat mengekspresikan kreativitasnya dalam menciptakan karya dari gelas plastik bekas. Hal ini disebabkan oleh rasa takut mencoba hal baru dan kurangnya pengalaman dalam berinteraksi dengan seni.